The Effect of Audio-Visual Media on The Front Roll Floor Exercise Skills of Phase B Students with Disabilities in Adaptive PE Learning - Alief Yanuar Rizky Faisal; Lukmannul Haqim Lubay; Mukhlisin; Eva Sri Gumilang (Universitas Negeri Semarang, 2025)
This study aims to examine the effect of audio-visual media on improving the forward roll floor exercise skills of Phase B deaf students in adaptive physical education. Students with hearing impairments face challenges in receiving verbal instructions, which often hinders their understanding of motor skills, especially in complex movements such as the forward roll. This quasi-experimental research used a one-group pretest-posttest design involving 10 students from a special education school. The intervention was conducted over 12 sessions using instructional videos accompanied by visual cues and progressive movement stages. Data were collected using an observation sheet and analyzed using descriptive and inferential statistics. The results showed a significant improvement in students’ motor performance after the implementation of audio-visual media. The integration of visual-based instruction helped students to better observe, imitate, and internalize movement techniques. This study confirms that audio-visual media is an effective strategy for supporting the learning needs of students with disabilities, especially those with sensory impairments. Moreover, it contributes to the development of inclusive and adaptive physical education practices by encouraging the use of technology to enhance instructional delivery and student engagement.